Single and mixed feline lungworm infections: clinical, radiographic and therapeutic features of 26 cases (2013–2015). Issue 10 (October 2017) - Crisi, Paolo E; Aste, Giovanni; Traversa, Donato; Di Cesare, Angela; Febo, Elettra; Vignoli, Massimo; Santori, Domenico; Luciani, Alessia; Boari, Andrea
Objectives: The aim of this study was to retrospectively describe clinical, radiographic and therapeutic features of feline lungworm infection. Methods: Medical records of cats with lungworm diagnosis, thoracic radiography and without concurrent diseases between 2013 and 2015 were reviewed. Collection of data included physical examination, haematology, serum biochemistry, therapy with a variety of anthelmintics and outcomes. Results: Thirty-seven records were recovered and 26 were included in the study. Single infections by Aelurostrongylus abstrusus (n = 15), Troglostrongylus brevior (n = 3) and Capillaria aerophila (n = 1) and coinfections by T brevior / A abstrusus (n = 6) and T brevior / C aerophila (n = 1) were diagnosed. The most common respiratory signs were coughing (n = 12), increased vesicular sounds (n = 10), dyspnoea (n = 9), such as laboured breathing, orthopnoea or open-mouth breathing, and tachypnoea (n = 6). Two cats were subclinically infected. The most common laboratory abnormality was anaemia (n = 7). Radiographic patterns recorded were interstitial (n = 24), bronchial (n = 21), alveolar (n = 10) and vascular (n = 2). Twenty-five cats had a complete recovery within 2–6 weeks of therapy. One kitten died 7 days after the diagnosis. Conclusions and relevance: Lungworms should always be included in the differential diagnosis in cats living in endemic areas and presenting with respiratory signs and radiographic abnormalities. A copromicroscopic examination should be considered as the first diagnostic step for all cats at risk of lungworm infections. In most cases, timely therapy with a variety of anthelmintics guarantees recovery.